Renewed occurrence of schooling scalloped hammerhead (Sphyrna lewini) and of great hammerhead (S. mokarran) sharks in the Cayman Islands - Gore, Mauvis; Kohler, Johanna; Ormond, Rupert; Gallagher, Austin; Fernandes, Teresa; Austin, Timothy; Pattengill-Semmens, Christy (Frontiers in Marine Science, 2024)
The scalloped hammerhead shark (Sphyrna lewini), a critically endangered species with a decreasing global population, is characterised by its occurrence in large schools. Such schools are still observed today in the Pacific Ocean, but this is generally not the case in the Atlantic Ocean, and in the Cayman Islands not since the 1970s. Here we report a recent record of a school of S. lewini in deep water off Grand Cayman, and describe a recent, concomitant increase in numbers of the species, and its critically endangered congener, the great hammerhead (Sphyrna mokarran), around the Cayman Islands. Relative population trends and seasonal patterns were assessed using data from shallow and deep-water BRUVS, scientific longlining, citizen science projects including the Sharklogger Network and REEF, and social media reports. It appears that S. lewini may be slowly re-occupying the area, selecting and using deeper waters to school, while S. mokarran has also become less scarce than hitherto 1 Introduction Large hammerhead sharks are among the most critically endangered shark species globally (Rigby et al. 2019a b). The scalloped hammerhead shark, Sphyrna lewini, has a maximum size of 370-420 cm total length (TL) (Ebert et al. 2013); females mature at 200-250 cm TL and males at 180-200 cm TL (Branstetter 1987;Hazin et al. 2001). It is considered a coastal and semi-oceanic pelagic species (Moore and Gates 2015). The species is currently classed in the IUCN Red List as critically endangered (CR A2bd), since the global population has undergone a steep decline, likely by >80%, and is severely fragmented (Rigby et al. 2019a). The decline is principally the consequence of being caught globally as both target and bycatch in pelagic commercial and small-scale longline, purse seine, and gillnet fisheries, in which it may be retained for both meat and fins (Rigby et al 2019a). In the Northwest Atlantic and Gulf of Mexico S. lewini appears to have been overfished between 1983